Concentration and distribution of Linear alkylbenzenes in surface sediments of South China Sea as molecular markers for sewage pollution - Ebrahim, Najat Abdullah (2011)
The coastal areas along the South China Sea (SCS) have been polluted by pollutants from various sources such as sewage outfalls and storm drains. Differentiating between these inputs is important in order to create better management of coastal resources. Linear alkylbenzenes (LABs), raw materials in the production of detergents, have been recognized as molecular markers for domestic waste inputs for more than a decade. Due to the hydrophobic characteristic of LABs, its residues will remain in detergents, survive wastewater treatment, and can be transported into the environment with treated sewage. Hence, a study was carried out at selected coastal areas along the SCS to determine the concentration of LABs in sediment. Thirty sampling stations were chosen from the location in the east coast of Peninsular Malaysia area onward to SCS region. Gas chromatography-mass spectrometry (GC-MS) was used to quantitate LABs of different sediment as well as sediment from different locations. The types of LABs compounds found in the samples were 1-pentylhexyl, 1-butylhexyl, 1-propylhexyl, 1-propylheptyl, 1-ethyloctyl, 1-methylnonyl, 1-propyloctyl, 1-ethylnonyl, 1-methyldecyl, 1- pentylheptyl, 1-butyloctyl, 1-propylnonyl, 1-ethyldecyl, 1-methylundecyl, 1-pentyloctyl, 1-hexylheptyl, C-19 LABs compound 1, C-19 LABs compound 2, C-19 LABs compound 3. Total LABs concentration in the surface sediments ranged from 1191.73 to 206.06 ng/g dry weight. Among the 30 stations, Terengganu, seems to be the most concentration with LABs, followed by Pahang, Johor and finally Kelantan. I/E ratios (a ratio of internal to external isomers of LABs) for SCS ranged from 0.12 to 5.68. I/E ratios at Kelantan were much lower than the others, indicating that sewage discharged at Kelantan is poorly treated. I/E ratios can be used to determine the degree of biodegradation of LABs in a range of environments, making it a powerful yet simple tool for monitoring biodegradation of LABs in the environment.